Prevalence and molecular characteristics of ESBL and AmpC β -lactamase producing Enterobacteriaceae strains isolated from UTIs in Egypt - Mohamed, Ebtisam S. (Antimicrob Resist Infect Control, 2020)
BACKGROUND: Infections caused by Enterobacteriaceae are mainly treated with the β-lactam antibiotics, nevertheless, the emergence of species with plasmid-borne β-lactamases has decreased the efficacy of these antibiotics. Therefore, continuing studies on the resistance pattern of different regions is important for assessment of proper antimicrobial therapy protocols. The study aimed to characterize extended-spectrum β-lactamase (ESBL) and AmpC β –lactamase (AmpC) producing Enterobacteriaceae isolated from community-acquired UTIs in Egypt. METHODS: Out of 705 urine samples, 440 Enterobacteriaceae isolates were investigated to detect ESBL and AmpC β -lactamases producers by phenotypic and molecular methods. RESULTS: Out of 440 Enterobacteriaceae isolates, 311 were identified as ESBL producers by phenotypic testing. ESBL genes were detected in 308 isolates. BlaCTX-M-type was the most prevalent 254 (81.6%), out of them blaCTXM-15 was the commonest (152, 48.8%) followed by blaCTX-M-1 (140, 45%), blaCTX-M-8 (72, 23.1%) and lastly blaCTX-M-2 (4, 1.3%). blaTEM gene also was detected in a high rate (189, 60.7%). Two hundred and thirty-five (75.5%) of ESBL producers harbored blaCTX-M in combination with blaTEM and/or blaSHV genes. Multiple drug resistance in the ESBL-producers was significantly (P < 0.05) higher than in non–ESBL producers. Imipenem was the most effective drug against ESBL producers. Among 35 cefoxitin resistant isolates, 18 (51.4%) identified as carrying AmpC genes by multiplex PCR. Within AmpC β -lactamase genes, DHA gene was the predominant gene (15, 42.3%). CIT and MOX genes were also present, but in a low rate (5, 14.2% and 4, 11.4%) respectively. Co-existence of multiple AmpC genes was detected exclusively in K. pneumoniae isolates. E. coli isolates harbored DHA gene only. However, FOX gene was not detected in the study isolates. Seventeen of isolates carrying AmpC genes were also positive for ESBL genes. CONCLUSION: The study shows that the prevalence of ESBL producing Enterobacteriaceae spread in south Egypt is alarming, however AmpC β -lactamase production is not so high.